Setting the Benchmark: A Comparative Analysis of Research Performance Indicators between Leading World Research Universities and Top-Ranked Research Universities in Malaysia - Kwan, Yee Min; Muhamad, Fadillah; Chin, Mui Yin (Journal of Research Management and Governance, 2024)
The National Higher Education Strategic Plan 2007-2020 and the Malaysia Education Blueprint (Higher Education) 2015-2025 aim to strengthen research and innovation in Malaysian universities, positioning them as world-class institutions. As a result of these national initiatives, six Malaysian universities have been ranked among the top 500 in the Times Higher Education (THE) World University Rankings 2024. This paper examines the institutional research performance of the top-ranked Malaysian universities in comparison to the leading world universities. Ten top-ranked world and Malaysian universities were identified based on the Times Higher Education World University Rankings 2024. Bibliometric indicators from Elsevier's SciVal were used to compare research performance among these universities from 2018 to 2023. The results indicate that the leading world universities outperform the top-ranked Malaysian universities in areas such as scholarly output, citation counts, and research impact measured by citations and publication in top journal percentiles. They are pioneers in their respective subject areas, with citations of their publications being twice the world average. Malaysian universities are active in international co-authorship but show lower impact, reflecting a growing yet developing academic influence compared to leading world universities. The publication landscape of the world's leading universities is dominated by the subject areas of Medicine, and Physics and Astronomy. Malaysian universities demonstrate a broader range of subject area preferences, with a strong emphasis on Engineering. By benchmarking against the world's leading institutions, Malaysian universities can identify areas for research improvements to enhance their world rankings.